Safety of Health Care Workers A Priority for Patient Safety - Maiga Ayub Hussein; Chebet Frida; Dwi Sutiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Worldwide healthcare workforce represents 12%, in Uganda, out of the 39000 healthcare workers (HCW), 500 have been deployed at Mbale regional referral hospital (MRRH). The deficient quality service delivery is attributed to adverse occupational health risk that are not addressed and acknowledged posing a great risk to patient safety. Study aims to investigate the unsafe acts and unsafe working conditions of health care workers at (MRRH).Methods: A quantitative observational study with a cross-section design was used using and a semi structured observation checklist for data collection among 120 health care workers of MRRH.Result: 45(37.5%) of the HCW never wore the necessary PPEs versus 75(62.5%) who wore, almost half 55(45.3%) worked over time and 65(54.6%) did not, as well the same figures represent those who over worked and those who did not over work respectively. 70% of the working places had defective working conditions for example no lighting, slippery floors and no danger signs. 75% of the wards had improper waste segregation measures.Conclusion : HCW and institutions should intervene to mitigate the hazards, strengthening occupational health, patient safety, hazard prevention and control